Uchwycić stratę, albo „kamyki cmentarne” z Melbourne - Katarzyna Kwapisz-Williams (Postscriptum Polonistyczne)
Migration always involves loss, which inspires potential writers and is itself often the focus of migrants’ narratives. Seen through this monodimensional attachment to things left behind and hence not particularly valued, written and unwritten stories of migrants’ experiences are themselves prone to disappear, together with the memory of their authors. This paper examines the work of a biographer and poet, Bogumiła Żongołłowicz, commited to recovering and preserving achievements of Polish postwar migrants in Australia, reclaiming forgotten or unappreciated literary works for future readers, and celebrating life and memory of those who would otherwise perish as well.